2018
DOI: 10.1002/ente.201800133
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance Evaluation of Flame Retardant Additives for Lithium Ion Batteries – II. Full Cell Cycling and Postmortem Analyses

Abstract: Within this 2 nd part of a comparative study five flame retardant additives (FRs) as candidates for lithium ion battery (LIB) electrolytes are evaluated in terms of their electrochemical performance in order to investigate performance differences and their long-term stability. FRs from four different phosphorus-containing molecule classes, (namely tris(2,2,2-trifluoroethyl)phosphate (TFP), tris(2,2,2-trifluoroethyl)phosphite (TTFPi), bis(2,2,2-trifluoroethyl)methylphosphonate (TFMP), (ethoxy)pentafluorocyclotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…Furthermore, additives (up to 5%, either by v/v or w/w) [93] can be applied to further modify the different electrolyte properties. These modifications include flame retardancy [28][29][30][94][95][96] or the enhanced formation of SEI and CEI [97][98][99][100][101][102]. During the first charge/discharge cycles, also called formation cycles, the SEI is formed and, thus, further prevents decomposition of electrolyte at the Cathode materials can be divided into three structural groups: one-dimensional materials (e.g., olivine structures) with a highly anisotropic lithium diffusion in a single direction, two-dimensional materials (layered structures) allowing diffusion in two spatial dimensions, and three-dimensional materials (e.g., spinel structures) which allow diffusion in all three dimensions [72][73][74].…”
Section: Lithium Ion Battery Materials and Compositionmentioning
confidence: 99%
“…Furthermore, additives (up to 5%, either by v/v or w/w) [93] can be applied to further modify the different electrolyte properties. These modifications include flame retardancy [28][29][30][94][95][96] or the enhanced formation of SEI and CEI [97][98][99][100][101][102]. During the first charge/discharge cycles, also called formation cycles, the SEI is formed and, thus, further prevents decomposition of electrolyte at the Cathode materials can be divided into three structural groups: one-dimensional materials (e.g., olivine structures) with a highly anisotropic lithium diffusion in a single direction, two-dimensional materials (layered structures) allowing diffusion in two spatial dimensions, and three-dimensional materials (e.g., spinel structures) which allow diffusion in all three dimensions [72][73][74].…”
Section: Lithium Ion Battery Materials and Compositionmentioning
confidence: 99%
“…52 Among these five flame retardants it was shown that the fluorinated cyclophosphazenes (PFPN and FPPN) outperform the other additives (phosphates, phosphites and phosphonates) both in terms of electrolyte safety and electrochemical performance. 53 Although the fluorinated cyclophosphazenes are most expensive, they are promising for future investigations. Future work on this electrolyte may include the application in larger cells and compatibility with other electrode configurations.…”
Section: Non-flammable Additives (Fire Retardant or Completely Non-flammable) (R10%)mentioning
confidence: 99%
“…Discovery and development of novel functional materials with targeted properties traditionally involves a large number of trial tests following a series of procedures, see, e.g., on flame retardants for liquid electrolytes. [14][15][16][17] However, these efforts are inevitably far from time-efficient considering the near infinite chemical space. Current materials design approaches are still mostly based on human knowledge and intuition, as well as on low throughput experiments.…”
Section: Accelerating the Search For Functional Materials Is An Ongoi...mentioning
confidence: 99%